Evaluation of Electronic Voting Requirements and Evaluation Procedures to Support Responsible Election Authorities - Volkamer, Melanie (Lecture Notes in Business Information Processing, 2009)
Electronic voting has a young and attractive history, both in the design of basic cryptographic methods and protocols and in the application by communities who are in the vanguard of technologies. The crucial aspect of security for electronic voting systems is subject to research by computer scientists as well as by legal, social and political scientists. The essential question is how to provide a trustworthy base for secure electronic voting, and hence how to prevent accidental or malicious abuse of electronic voting in elections. To address this problem, Volkamer structured her work into four parts: "Fundamentals" provides an introduction to the relevant issues of electronic voting. "Requirements" contributes a standardized, consistent, and exhaustive list of requirements for e-voting systems. "Evaluation" presents the proposal and discussion of a standardized evaluation methodology and certification procedure called a core Protection Profile. Finally, "Application" describes the evaluation of two available remote electronic voting systems according to the core Protection Profile. The results presented are based on theoretical considerations as well as on practical experience. In accordance with the German Society of Computer Scientists, Volkamer succeeded in specifying a "Protection Profile for a Basic Set of Security Requirements for Online Voting Products," which has been certified by the German Federal Office for Security in Information Technology. Her book is of interest not only to developers of security-critical systems, but also to lawyers, security officers, and politicians involved in the introduction or certification of electronic voting systems.